Fractionation and characterization of antioxidant peptides from rice bran protein hydrolysates stimulated by in vitro gastrointestinal digestion - Suphat Phongthai (2020)
© 2020 Cereals & Grains Association Background and objective: Rice bran protein concentrate was prepared and hydrolyzed by using pepsin–pancreatin. The obtained result was further filtered through 5-kDa membranes. A permeate was collected and sequentially fractionated by different chromatographic techniques. The peptide fractions were determined for the antioxidant activities. Findings: Three peptide fractions were derived after separating the crude protein hydrolysates by anion-exchange chromatography. Due to its highest ABTS radical scavenging and metal chelating activities (p <.05), fraction F2-A was pooled and separated further by size-exclusion chromatography (SEC). Among the SEC fractions, F1-S showed strongest antioxidant activities; thus, it was collected for reverse-phase HPLC purification. Subsequently, the peptide fractions were successfully separated and F4-H had the greatest ABTS-scavenging activities (214.61 µmol Trolox/g sample, respectively). In addition, it displayed the strongest ability to reduce ferric to ferrous ions (104.80 µmol FeSO4/g sample) (p <.05), while F1-H showed the highest ability to chelate metal ions (266.40 µmol EDTA/g sample) (p <.05). Conclusion: These results demonstrate that hydrophobic amino acids play a major role in scavenging free radicals, whereas polar amino acids are responsible for reducing and chelating metal ions. Significance and novelty: Rice bran protein composes of high ratio of hydrophobic amino acid. It is a suitable source of antioxidant peptides that might be produced during gastrointestinal digestion. Separation and purification using chromatographic techniques showed promising results for selectively fractionate antioxidant peptides with specific activity.